Fiscal Monitor, October 2016 : Debt: Use It Wisely - Moreno Badia, Marialuz (Fiscal Monitor; Fiscal Monitor ;, 2016)
Drawing on an expanded data set covering emerging markets and low-income countries as well as advanced economies, this issue examines the extent and makeup of global debt and asks what role fiscal policy can play in facilitating the adjustment. The analytical framework explicitly models the interlinkages between private and public debt in analyzing the role of fiscal policy in the deleveraging process. Country case studies provide useful insights on what fiscal policy should and should not do to facilitate deleveraging while minimizing the drag on the economy.